SAT0027 Inhibition of Tlr7 and Tlr8 Signaling by Antagonizing Micro-Rna Derived from Extracellular Vesicles Suppresses Inflammation in A Novel Human-Mouse Chimeric Model of Lupus. (15th July 2016) - Young, N.A.; Valiente, G.; Hampton, J.; Steigelman, H.; Jarjour, W.
Abstract : Background: Systemic lupus erythematosus (SLE) is a prototypic autoimmune disease affecting multiple organs and displaying a heavy female predominance during reproductive years. Our previous studies have demonstrated that toll-like receptor (TLR)7 and TLR8 are significantly up-regulated in peripheral blood mononuclear cells (PBMCs) of SLE patients and induced with estrogen treatment. While the conventional role of TLR7 and TLR8 involves binding to single-stranded RNA of viral origin to stimulate innate inflammatory responses, recent work has identified specific micro-RNAs (miRs) capable of activating these receptors that are packaged and secreted in exosomes. Objectives: The goal of this study was to explore the therapeutic potential of using a cocktail of miR antagonists to block TLR7 and TLR8 inflammatory pathways induced by extracellular vesicle (EV)-derived miRs in SLE. Methods: PBMCs from active SLE patients were adoptively transferred into immunodeficient NOD-scid IL-2rγ (null) mice to produce chimeras using a similar protocol we have previously established for Sjöjren's syndrome. PBMCs were treated with a cocktail of locked nucleic acid miR antagonists or nonsense, scrambled RNA control prior to injection. Blood was collected for both flow cytometry and cytokine analysis and tissues were processed for histopathological examination by H&E and immunohistochemistry. Results: 21 days after adoptive transfer, human T-cells (CD4+ and CD8+), B-cells, monocytes, and NK cells were all successfully recovered from whole blood of chimeric mice at similar levels in both treatment groups. However, miR inhibition reduced levels of human IL-2, IL-6, IL-10, and TNF-α when compared to scramble (control) treatment. Although histopathological analysis revealed little to no inflammation in the skin and ear, miR inhibition blocked the robust responses detected in the small intestine, liver, and kidney with scramble RNA (control) treatment. Immunohistochemical analysis of the infiltrates confirmed the presence human CD3+ T-cells in these tissues and further demonstrated the suppression of inflammation following miR inhibition. Conclusions: These results establish a novel chimeric model to study SLE and provide a platform to further explore the therapeutic efficacy of suppressing EV-encapsulated miRs that bind to TLR7 and TLR8 to induce autoimmune-mediated inflammatory responses. References: Fabbri M, Paone A, Calore F, Galli R, Gaudio E, Santhanam R, et al. MicroRNAs bind to Toll-like receptors to induce prometastatic inflammatory response. Proceedings of the National Academy of Sciences of the United States of America 2012, 109(31): E2110–2116. Young NA, Wu LC, Burd CJ, Friedman AK, Kaffenberger BH, Rajaram MV, et al. Estrogen modulation of endosome-associated toll-like receptor 8: an IFNalpha-independent mechanism of sex-bias in systemic lupus erythematosus. Clinical immunology 2014, 151(1): 66–77. Young NA, et al. A chimeric human-mouse model of Sjogren's syndrome. Clinical immunology, 2014;156:1–8. Acknowledgement: We would like to extend our appreciation to all the volunteers that participated in this study and thank the Center for Clinical and Translational Science/Research Match program at The Ohio State University Wexner Medical Cetner and the American Red Cross. Disclosure of Interest: None declared